An Investigation of Acoustic Emission Signal Attenuation for Monitoring of Progressive Failure in Fiberglass Reinforced Composite Laminates - Z. M., Hafizi; Epaarachchi, J.; Lau, K. T. (Universiti Malaysia Pahang, 2013)
Glass fiber reinforced polymer (GFRP) laminates have a high damping characteristic which can retard ultra-high frequency guided wave signals from propagating along the plate. Owing to this, the identification of an effective area for sensor location is essential. Appropriate signal processing, including wavelet analysis was done, in order to observe the details of an acoustic emission (AE) signal which was emitted at a distance from it source. This study reveals that it is necessary to consider the near field and far field effects of AE signal attenuation, in particular, to determine a composite's micro failure characterization. Consequently, this attenuation behavior was used to develop the non-velocity based source mapping to monitor the progressive failure in composite laminates. This paper details the outcomes of the signal energy attenuation method with an improved algorithm for progressive failure monitoring in fiberglass reinforced composite laminates and the 'effective length' for better AE detection.